Factors Related to Behavior in Implementing Patient Safety of Nurses - Sugianto, Indra Adi; Rahayu, Sri (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Patient safety is an important component in care and measures to improve the quality of service quality. The strategy of implementing patient safety has been carried out with various efforts in the hospital environment. The highest number of patient safety data by province in Banten is 125 reports, and Jakarta is 105 reports. This study aimed to determine factorfactors related to the behavior of the application of patient safetyto the nurses the Emergency Room Installation of RSUD dr. Dradjat Prawiranegara in 2018.The study design was cross sectional in which the samples were taken by total sampling method. The study ofpopulation were nurses in the emergency room of RSUD dr. Dradjat Prawiranegara Serang numbered 37 people. Data collection useda questionnaire. Univariate research results showed that of 37 respondents 30 respondents (81.1%) had a good level of knowledge, 21 respondents (56.8%) had positive attitudes, 30 respondents (81.1%) had years of service≥5 years, and 20 respondents (54.1%) have good behavior. Bivariate analysis results showed that there was a significant relationship between knowledge (p value = 0.002), attitude (p value = 0.003) and work period ≥5 years (p value = 0.027) with the application of patient safety behavior to nurses. Researchers expect that the hospital able to refresh the application of patient safety to all nurses on a regular basis every six months.